57.1k views
4 votes
Simplify this expression: 19 - (-8) - (-14) = ? A. 41 B. 25 C. -7 D. -3

User Andreask
by
5.5k points

2 Answers

4 votes

Answer:


\mathrm{A.} \: 41

Explanation:


19 - (-8) - (-14)


\mathrm{Apply \: rule:} \: -(-a)=a


19+8+14


\mathrm{Add \: the \: numbers.}


=41

User Bunji
by
5.7k points
4 votes

Answer:

A. 41

Explanation:

19 - (-8) - (-14) =

19+8+14

Remember: Two negatives=One positive ;)

27+14

41

A. 41

User Afreekano
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.